Effects of Training and Development on Employee Performance and Social Productivity: A Case Study of IT Sector - Gupta, Santosh Kumar (Journal of Commerce and Trade, 2022)
Now days, organization and individual should develop and progress all together for their survival and accomplishment of mutual goals. So, every modern management must develop the organization through human resources development. Human resources development including training and developments helps in enhancing internal capabilities of an organization to deal with current or future challenges effectively. The purpose of this paper is to investigate whether training and development has impact on employees’ performance and productivity. This paper is descriptive in nature, and data has been collected through various primary and secondary sources. The methodology was based on a questionnaire survey to collect the data, the study obtained information from one hundred ten (110) respondents from IT Sector. Two Hypotheses are developed to see the Influences of all the independent variable on the overall employees’ performance and productivity. Both hypotheses were examined through SPSS. The major finding of the study is that training and development positively influence the employee’s performance & productivity.